Nitrogen and Phosphorus Balances Vary at the Whole-Farm, Field, and Within-Field Scales - Berlingeri, Jonathan M.; Lawrence, Joseph R.; Sunoj, S.; Czymmek, Karl J.; Ketterings, Quirine M. (Frontiers in Sustainability, 2021)
A field nutrient balance (supplied minus harvested) can be an effective, end-of-season management evaluation tool. However, development of guidance for balance-based management requires knowledge of variability in balance inputs. To contribute to development of such guidelines, we evaluated the impact of corn silage hybrid selection, nutrient management, and growing conditions on field nitrogen (N) balances and documented variability in N and phosphorus (P) balances at the whole-farm, field, within-field levels. Variability in N removal among hybrids was evaluated using hybrid trials (5 locations, 4 years each). Variability in farm and field balances (4 farms, 2 years each) and within-field balances (2 farms, 2 years each) was assessed as well. Nitrogen supply comprised soil N (soil type-specific book values), rotation N, past manure N, and current year N (fertilizer and/or manure). Total N balances included all current year manure N while available N balances considered only plant-available N from manure. Phosphorus balances were derived as total P applied minus P harvested. Yield explained 81% of the variability in N uptake across hybrids. Nitrogen uptake intensity (NUI; N uptake per unit of yield) varied across locations and years, averaging 4.3 ± 0.1 kg N/Mg for short-season hybrids (≤ 95 days-to-maturity [DTM]) versus 4.1 ± 0.1 kg N Mg-1 for longer-season hybrids. Whole-farm N balances ranged from 139 – 251 kg N ha-1 for total N and 43 – 106 kg N ha-1 for available N. Phosphorus balances ranged from 28 – 154 kg P ha-1. Balances per field ranged from -8 – 453 kg N ha-1, -66 – 250 kg N ha-1, and -30 – 315 kg P ha-1 for total N, available N, and total P, respectively, while within-field balances showed even larger ranges. We conclude that (1) variability in corn silage N and P balances at field and within-field scales and across year is large, emphasizing the need for field and within-field (where feasible) evaluation tools and management options, and (2) feasible limits for N balances should include both total and available N.